The value of ultrasound to differentiate between benign and malignant duct ectasia - AL -Tememy, Enam A.; Ahmad, Laith; AL-Shaheen, Zainab O.; Jabbar, Jinan A. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Mammary duct ectasia is defined as dilated duct larger than 2 mm in diameter seen in fibrocystic changes, ductal epithelial hyperplasia, papiloma, DCIS. US has a significant role in diagnostic breast imaging. It is most commonly used as an adjunctive test in characterizing lesions detected by other imaging modalities or by clinical examinationObjective: This study was designed to investigate differences in ultrasonographic findings between malignant and benign mammary duct ectasia.Patients and Methods: From November 2010 to July 2011, 100 womem with mammary duct ectasia lesions depicted on sonograms were included in this study. We evaluated the ultrasonographic (US) findings in terms of involved ductal location, size, margin, intraductal echogenicity, presence of an intraductal nodule, calcification, ductal wall thickening and echo changes of the surrounding breast parenchyma. The US findings were correlated with the pathological features.Results: Of the 100 lesions, 84 lesions were benign and 16 lesions were malignant. Benign lesions include: an inflammatory change (n=14), ductal epithelial hyperplasia (n=6), fibrocystic change (n=54), intraductal papilloma (n=10). Malignant lesions include: ductal carcinoma in situ (DCIS) (n=2), infiltrating ductal carcinoma (n=14). On US images, the peripheral ductal location, an ill-defined margin, ductal wall thickening and a hypoechoic change of the surrounding parenchyma were features significantly associated with malignant duct ectasia.Conclusion: For ill-defined peripheral duct ectasia with ductal wall thickening and surrounding hypoechogenicity as depicted on US, the possibility of malignancy should be considered and radiologists should not hesitate to recommend a prompt biopsy.